A permutation parallel algorithm under exchange restriction with message passing interface - Karim, Sharmila; Omar, Zurni; Ibrahim, Haslinda (2014)
The permutation generation method is based on starter sets generation under exchange operation and exploited it for listing down all n! Permutations. However permutation generation is time consuming process, the implementation of sequential algorithm to parallel computation is the option for reducing the computation time. The sequential algorithm is implemented to a parallel algorithm by integrating with Message Passing Interface (MPI) libraries by paralleling the starter sets generation task.The speedup and efficiency is the indicator tool for analyzing performance of this parallel algorithm.The results show reduction time computation of parallel algorithm among processors.